(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the characteristics of fracture lines after BSSO classified by the lingual split scale (LSS) through the analysis of 3D images. Subjects and methods: A cross-sectional descriptive study was conducted on 28 patients diagnosed with maxillofacial asymmetry who underwent BSSO orthognathic surgery from November 2025 to February 2026 at the Department of Plastic and Aesthetic Surgery, National Hospital of Odonto-Stomatology, Hanoi. All surgeries were performed by a single surgeon. Postoperative CT scans were taken within one week to evaluate the lingual fracture patterns and inferior border cuts. Results: LSS I was the dominant pattern, representing 76.8% of cases, followed by LSS III (21.4%) and LSS II (1.8%). The fracture patterns exhibited a high degree of bilateral symmetry, with 78.6% of patients having the exact same LSS pattern on both the left and right sides.,and no unfavorable fractures (LSS IV) were recorded during the study. Conclusion: Evaluating BSSO surgery using 3D imaging combined with the LSS scale allows for an effective qualitative assessment of surgical outcomes. The findings demonstrate that the LSS I fracture pattern, commonly associated with an inferior border cut pattern A, is the most predictable surgical result and presents with significant bilateral symmetry.